ANALISIS PROMOSI DALAM UPAYA MEMPERKENALKAN POTENSI PARIWISATA KOTA BEKASI (Studi Kasus Dinas Pemuda, Olahraga, Kebudayaan dan Kepariwisataan Kota Bekasi) - Siti Khadijah (Fakultas Komunikasi, Sastra, dan Bahasa, 2012)
The development in tourism has several impacts – supporting the society’s economic growth, preserving the cultural and art legacy, increasing the local revenue dan involving all stakeholders in synergy. Bekasi has tourism potential which can be seen from the availabilty and variety of tourism products such as family recreations, shopping arcades, historical tours, educational and cultural tours, and industrial tourism, but the number of local tourists visit is only 7.1% of the total Bekasi’s population number. Impact of tourism development has increased the welfare of the community, maintaining the cultural heritage and artistic heritage, increasing revenue (PAD) and involving all stakeholders in synergy. Bekasi has tourism potential, seen from the availability and variety of tourism products such as family recreation attractions, shopping malls, historical tours, educational tours and cultural and tourism industries, but the number of local tourists visit only 7.1% of the total population numbering 21 Bekasi thousand people. Lack of promotion and efforts to introduce tourism products Bekasi to tourists and local communities, has been a problem in developing local tourism. The result shows that Bekasi has the cultural and artistic heritage. However, the condition of the cultural site is not well-maintained. Bekasi City Government activities, particularly by promoting Bekasi Disporbudpar so far has not been maximized. Activities undertaken only 2 (two), which follows the exhibition organized by the election of brother Mpok APEKSI and Bekasi. The relationship between the promotion of Bekasi tourism with an increasing number of tourists visiting Bekasi is not significant. The number of local and foreign tourists do not show the numbers mean. Factors affecting the increase in tourism visits Bekasi is the unavailability of tourism products that can attract tourists both local and international. As a result, the tourism industry in Bekasi is slow